Are markets interested in adapting to climate? Insights from Singapore - WHITTAKER, Stella (Institutional Knowledge at Singapore Management University, 2023)
We have collected the views of leading practitioners and academics in Singapore involved in funding and financing urban climate change adaptation1 (thereon referred to as urban adaptation). Throughout this paper we discuss several vital perspectives on adaptation financing, namely responsibility for adaptation investment, the extent of government adaptation investment, private sector adaptation investment appetite and prospects for experimentation in adaptation financing. We also attempt to shed light on the existence or not of an adaptation financing gap2 in Singapore.